Spatial and Temporal Patterns of Stony Coral Tissue Loss Disease Outbreaks in The Bahamas - Dahlgren, Craig; Pizarro, Valeria; Sherman, Krista; Greene, William; Oliver, Joseph (Frontiers in Marine Science, 2021)
Coral reefs of Grand Bahama and New Providence islands in The Bahamas have been surveyed several times over the past decade, and long-term monitoring indicates declines in coral cover associated with hurricanes, bleaching events, and local threats. However, the greatest declines in coral populations in The Bahamas over the past decade may be attributed to the recent introduction of stony coral tissue loss disease (SCTLD). In 2019, a comprehensive assessment of both islands was conducted using Atlantic and Gulf Rapid Reef Assessment (AGRRA) methods to characterize reefs before SCTLD was reported in The Bahamas. Following reports of SCTLD in late 2019, timed roving diver assessments of corals were conducted for Grand Bahama in March 2020 and New Providence in June 2020 to determine which species were affected by the disease and the proportion of corals that were healthy, infected with SCTLD, and those that appeared to have experienced recent mortality for the most abundant intermediate or highly susceptible species. Additional surveys were conducted for both islands in January 2021 to further assess the extent of the outbreak, and repeated assessments of several sites for each island were used to determine the impact of the disease on corals over the previous 6.5 to 10.5 months. Infection rates varied among species following patterns described for Florida and elsewhere, with higher infection rates occurring in vulnerable species for both Grand Bahama and New Providence. Pseudodiploria strigosa appears to be the most affected species with 45.6% of colonies on Grand Bahama infected and 23.1% infected on New Providence and recent mortality rates of 31.5 and 42.7%, respectively, at the time of surveys. Spatial patterns of mortality and infection rates for the most vulnerable species were greatest close to international commercial shipping ports on both islands, suggesting SCTLD has been present in those locations for a longer time, and the proportion of healthy colonies increased with distance from the port. For Grand Bahama, there was also a significant effect of depth, with shallow reefs having a higher proportion of colonies that was infected or experienced recent mortality. For New Providence, sites to the east of the port saw a sharp decline in infection and mortality rates with distance compared to sites west of the port, where nearly the entire coastline was affected by SCTLD. Temporal analyses showed an increase in recent mortality and a decrease in active infection for most species on both islands, but little change in the proportion of healthy corals, suggesting some degree of resistance to the disease. Because Freeport and Nassau are the two largest container ports in The Bahamas and are over 200 km apart with multiple islands between them where SCTLD has not yet been reported, it is probable that SCTLD arrived in The Bahamas via commercial shipping, followed by rapid spread within islands via local currents and other vectors. Results from this study stress the need for early detection and suggest that preventing the spread of the disease between islands via vessel traffic is of utmost importance.